Index: The Book of Statistical ProofsStatistical ModelsUnivariate normal dataAnalysis of variance ▷ Sums of squares in one-way ANOVA

Theorem: Given one-way analysis of variance,

sums of squares can be partitioned as follows

\label{eq:anova1-pss} \mathrm{SS}_\mathrm{tot} = \mathrm{SS}_\mathrm{treat} + \mathrm{SS}_\mathrm{res}

where \mathrm{SS} _\mathrm{tot} is the total sum of squares, \mathrm{SS} _\mathrm{treat} is the treatment sum of squares (equivalent to explained sum of squares) and \mathrm{SS} _\mathrm{res} is the residual sum of squares.

Proof: The total sum of squares for one-way ANOVA is given by

\label{eq:anova1-tss} \mathrm{SS}_\mathrm{tot} = \sum_{i=1}^{k} \sum_{j=1}^{n_i} (y_{ij} - \bar{y})^2

where \bar{y} is the mean across all values y_{ij}. This can be rewritten as

\label{eq:anova1-pss-s1} \begin{split} \sum_{i=1}^{k} \sum_{j=1}^{n_i} (y_{ij} - \bar{y})^2 &= \sum_{i=1}^{k} \sum_{j=1}^{n_i} \left[ (y_{ij} - \bar{y}_i) + (\bar{y}_i - \bar{y}) \right]^2 \\ &= \sum_{i=1}^{k} \sum_{j=1}^{n_i} \left[ (y_{ij} - \bar{y}_i)^2 + (\bar{y}_i - \bar{y})^2 + 2 (y_{ij} - \bar{y}_i) (\bar{y}_i - \bar{y}) \right] \\ &= \sum_{i=1}^{k} \sum_{j=1}^{n_i} (y_{ij} - \bar{y}_i)^2 + \sum_{i=1}^{k} \sum_{j=1}^{n_i} (\bar{y}_i - \bar{y})^2 + 2 \sum_{i=1}^{k} (\bar{y}_i - \bar{y}) \sum_{j=1}^{n_i} (y_{ij} - \bar{y}_i) \; . \end{split}

Note that the following sum is zero

\label{eq:anova1-pss-s2} \sum_{j=1}^{n_i} (y_{ij} - \bar{y}_i) = \sum_{j=1}^{n_i} y_{ij} - n_i \cdot \bar{y}_i = \sum_{j=1}^{n_i} y_{ij} - n_i \cdot \frac{1}{n_i} \sum_{j=1}^{n_i} y_{ij} \; ,

so that the sum in \eqref{eq:anova1-pss-s1} reduces to

\label{eq:anova1-pss-s3} \sum_{i=1}^{k} \sum_{j=1}^{n_i} (y_{ij} - \bar{y})^2 = \sum_{i=1}^{k} \sum_{j=1}^{n_i} (\bar{y}_i - \bar{y})^2 + \sum_{i=1}^{k} \sum_{j=1}^{n_i} (y_{ij} - \bar{y}_i)^2 \; .

With the treatment sum of squares for one-way ANOVA

\label{eq:anova1-trss} \mathrm{SS}_\mathrm{treat} = \sum_{i=1}^{k} \sum_{j=1}^{n_i} (\bar{y}_i - \bar{y})^2

and the residual sum of squares for one-way ANOVA

\label{eq:anova1-rss} \mathrm{SS}_\mathrm{res} = \sum_{i=1}^{k} \sum_{j=1}^{n_i} (y_{ij} - \bar{y}_i)^2 \; ,

we finally have:

\label{eq:anova1-pss-qed} \mathrm{SS}_\mathrm{tot} = \mathrm{SS}_\mathrm{treat} + \mathrm{SS}_\mathrm{res} \; .
Sources:

Metadata: ID: P376 | shortcut: anova1-pss | author: JoramSoch | date: 2022-11-15, 16:59.